El Excentrico, 1976-03-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, CA; Garcia Printing, 2024)
March 5, 1976 [5 de marzo de 1976]. Ano 26, No 23. Cover contains a photo of four construction workers working on a project. The headline reads, "Ser/OIC Vocational Training Programs."